Effect of Credit Easing Policy on Recovery of Iran's Economy: Stochastic Dynamic General Equilibrium Model Approach - Hadiseh Mohseni; Nabi Shahikitash; Mosayeb Pahlavani; Seyed Hossein Mirjalili (Quarterly Journal of Applied Economics Studies Iran, 2023)
By utilizing the new Keynesian stochastic dynamic general equilibrium model, this paper examines the effects of credit easing policy on macroeconomic variables with or emphasizing on production. For this purpose, a model has been design including 5 sectors of household, enterprises, banks, government and central bank. Considering the dominance of fiscal policy over monetary policy in the Iranian economy, the integrated constraint of the government and the central bank has been used. The model has been estimated using Bayesian method and quarterly time series data during 1991 to 2017. The results of Impulse Response Function show that implementation of this policy has increased consumption, investment, government spending and ultimately production, which indicates the effectiveness of this unconventional monetary policy to get the economy out of recession. Also, in response to the positive impulse of the central bank's credit line to banks and the negative impulse of legal reserves, bank facilities increase, which is in line with theoretical expectations. The impact of the negative impulse of interbank market rate has also led to an increase in production credits.
Keywords: 330; Recession; Credit Easing; DSGE Model; Credit Line; Bayesian Method